2003
DOI: 10.1016/s0022-5223(03)00074-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-mediated contact programs human mesenchymal stem cells to express cardiogenic phenotype

Abstract: In addition to soluble signaling molecules, direct cell-to-cell contact is obligatory in relaying the external cues of the microenvironment controlling the differentiation of adult stem cells to cardiomyocytes. These data indicate that human mesenchymal stem cells are plastic and can be reprogrammed into a cardiomyogenic lineage that may be used in cell-based therapy for treating heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(100 citation statements)
references
References 21 publications
4
93
1
2
Order By: Relevance
“…It apparently acts by modifying methylation [Momparler, 2005]. Other experiments studied coculture model of MSCs with neonatal cardiomyocytes [Lagostena et al, 2005] or cardiomyocyte-cell lines [Rangappa et al, 2003;Beeres et al, 2005], but not extensively with primary adult cardiomyocytes. We are presenting a study in controlled conditions of the effect of adult cardiomyocytes on the expression of markers of differentiation in MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It apparently acts by modifying methylation [Momparler, 2005]. Other experiments studied coculture model of MSCs with neonatal cardiomyocytes [Lagostena et al, 2005] or cardiomyocyte-cell lines [Rangappa et al, 2003;Beeres et al, 2005], but not extensively with primary adult cardiomyocytes. We are presenting a study in controlled conditions of the effect of adult cardiomyocytes on the expression of markers of differentiation in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, regarding heart repair, they have been shown to potentially originate both endothelial vascular cells and cardiomyocytes. Among the different strategies proposed to promote in vitro cardiac differentiation of MSCs, chronic exposure to 5-azacytidine has been amply tested [reviewed by Leri et al, 2005], as well as stimulation by exogenous cytokines and growth factors [Xaymardan et al, 2004, Shim et al, 2004, and coculture with neonatal cardiac cell [Lagostena et al, 2005] or immortalized cardiac cell lines [Rangappa et al, 2003]. Cocultures between MSCs and adult cardiomyocytes were performed mainly to show functional connection between the two cell types [Valiunas et al, 2004].…”
mentioning
confidence: 99%
“…It has also been demonstrated that BMSCs can differentiate into cardiac cell components and develop into functional phenotypes of myocardial cells within the microenvironment of the heart. 4 -6 Human mesenchymal stem cells cocultured with myocytes express myosin heavy chain, ␀-actin, and troponin T. 7 BMSCs can not only differentiate into myocytes but also improve left ventricular performance 8 and cause a significant reduction of infarct size when injected into the infarcted hearts or border zones of rats or mice. 5,6,9 Moreover, BMSCs can be delivered into the coronary artery, because they are capable of targeted migration and differentiation into cardiomyocytes in the scar tissue to improve cardiac function.…”
mentioning
confidence: 99%
“…Despite these differences in origin, several studies show that bone marrow-derived mesenchymal progenitor cells can acquire a cardiomyocyte phenotype under certain conditions in vitro and in vivo. These cells are capable of differentiating into cells with cardiomyocyte features in vitro, either through coculture with cardiomyocytes 44 or exposure to 5-azacytidine, 45 a cysteine analog capable of altering the expression of certain genes that may regulate differentiation. The cells are positive for b-myosin heavy chain, cardiac troponin T, a-cardiac actin and desmin.…”
Section: Mesenchymal Progenitor Cellsmentioning
confidence: 99%